Detection of chlorpyrifos in apples using gold nanoparticles based on surface enhanced Raman spectroscopy - Chen, Zhai; Yongyu, Li; Yankun, Peng; Tianfeng, Xu (International Journal of Agricultural and Biological Engineering, 2015)
In this study, gold nanoparticles (AuNPs) were synthesized for rapid and sensitive characterization and quantification of chlorpyrifos in apples. Min-max signal adaptive zooming and second derivative transformation method were adopted to pre-process Raman spectral signal. The min-max signal adaptive zooming method showed a higher correlation coefficient than derivative transformation when developing linear calibration curve between chlorpyrifos pesticide and Raman spectral peak intensity. The present method had a high reproducibility with the relative standard deviation less than 15%. Regression models showed a good linear relationship (R=0.962) between intensity of characteristic spectral peaks (at 677 cm-1) and chlorpyrifos concentration on whole apples ranging from 0.13 mg/kg to 7.59 mg/kg. The application of surface enhancement Raman spectroscopy (SERS) detected chlorpyrifos pesticide to the detection limit of 0.13 mg/kg, which can be applied further for lower concentration in the future. The method presented in this study can provide a way-out for detection of pesticide residue in whole apple to trace amount. Keywords: surface enhancement Raman spectroscopy, apple, chlorpyrifos, gold nanoparticles, pesticide detection DOI: 10.3965/j.ijabe.20150805.1771 Citation: Zhai C, Li Y Y, Peng Y K, Xu T F. Detection of chlorpyrifos in apples using gold nanoparticles based on surface enhanced Raman spectroscopy. Int J Agric & Biol Eng, 2015; 8(5): 113－120.